Forging Wargamers A Framework for Professional Military Education - Bae, Sebastian J. (Marine Corps University Press (MCUP), 2022)
How do we establish or improve wargaming education, including sponsors, participants, and future designers? The question stems from the uncomfortable truth that the wargaming discipline has no foundational pipeline, no established pathway from novice to master. Consequently, the wargaming community stands at a dangerous precipice at the convergence of a stagnant labor force and a patchwork system of passing institutional war-gaming knowledge. Unsurprisingly, this can lead to ill-informed sponsors, poorly scoped wargames, an unreliable standard of wargaming expertise, and worst of all, risks the decline of wargaming as an educational and analytical tool. This fundamental challenge is a recurring theme throughout this volume and each author offers their own perspective and series of recommendations.